Leis de Kepler do movimento planetário nos livros didáticos de física do Programa Nacional do Livro Didático de 2014: um estudo à luz de aspectos conceituais, didático-metodológicos e históricos - Oliveira, Paulo Henrique Portela (2015)
The Physics textbooks constitute the main teacher's working tool, although surveys indicate the need to prepare own teaching materials prepared by the teacher and the use of the textbook as support.We conducted a study of Kepler's Laws of Planetary Motion in Physics textbooks recommended by the National Textbook Program (PNLD in Portuguese) in 2014. The main objective is to verify how that content is addressed in these works. We use as conceptual, didactic-methodological and historical aspects analysis criteria. They are linked to that recommended by the PNLD Guide, the National Curriculum Guidelines for Secondary Education, and academic papers that focus urges that a History of Science in teaching Physics.The methodologywasqualitative in nature. We analyzed the 14 books of PNLD by analysis of the content. Based on our investigation, we concluded that the definition of concepts considered important for the understanding of the laws is not yet satisfied. We highlight the omission, in some books, the concept of the ellipse, which constitutes a basic element for learning content. Analysis of didactic and methodological aspects showed that contextualization is not included in the approach taken by textbooks, and interdisciplinary is attuned to the purpose of integrating the different areas of knowledge. About to the use of the History of Science, although it has an important role in learning in physics, is not present. There is no a concern with this aspect by most authors.